Electrical Device Protection from Overvoltage in a DC Power Supply Network: Fast-acting Protection, Realized by an “Artificial” Short Circuit in the Input of the Protected Device - Filipova-Petrakieva, S. K.; Shopov, Y. M. (Engineering, Technology & Applied Science Research, 2020)
In the present paper a protective device based on the so-called “artificial” short circuit in the input of the network, is proposed. To ensure the necessary time for switching on the protection, the increased power supply voltage is delayed to reach in the input of the protected device by additional inductance L, which is connected in series to the power supply. As a result of this forced short circuit, the DC-power supply is switched off by a standard protective circuit-breaker. The short circuit is realized by a fast-acting semi-conductor device (e.g. diac + thyristor, etc.). The controlling signal is formed as a voltage across a capacitor that is a part of RC-circuits connected in parallel to the DC-power supply network. An analytical expression for this voltage, using a classical method for transient analysis, is obtained. The main aim is to determine the exact time of switching on the protection. The research is confirmed with simulations by OrCAD PSpice under the exact values of the elements in the RC-circuits considered. Two rapid increase cases in the power supply voltage are considered: positive jump and linear increase. The suggested solution is applicable for overvoltage protection of different electrical devices. The electrical scheme, based on the electronic components, ensures a fast-acting breaking, which guarantees secure protection. Based on the analytical expressions, the synthesis of the circuit for control and protection is made and the respective values of its elements are calculated.